International accounting in Latin America: an overview of International Financial Reporting Standards (IFRS) - Robles Quiñónez, Gustavo Darío (2024)
The research aimed to examine the implementation of international financial reporting standards in Latin America. To achieve this, a comprehensive literature review was conducted, including theses, scientific articles, and the International Financial Reporting Standards Foundation website. The analysis indicates that the adoption of international financial reporting standards in the 18 countries studied is driven by the goal of aligning with global accounting practices and facilitating transparent financial reporting. The results suggest that while each country has its own accounting methods, adopting these standards prompts a convergence process and influences accounting procedures.